Family reunion : a novel - Thayer, Nancy, 1943- (Ballantine Books, 2021)
"A grandmother-granddaughter duo are eager to spend their summer together on peaceful Nantucket, but the season that unfolds brings about unforgettable surprises in New York Times bestselling author Nancy Thayer's magical, multigenerational novel. Eleanor Sunderland loves living on the Nantucket cliffside, in a charming home that has been in her family for decades. Now widowed, she looks forward to the arrival of her children and grandchildren for an annual family reunion, eager for the life and laughter that will soon fill the air. But Eleanor's island idyll is shattered when her money-driven children suggest she sell the house and move to a retirement community. She finds a lone ally in her twenty-two-year-old granddaughter, Ari, who moves in with her for the summer. Ari longs for a change of scenery, to stray from the path her parents have set for her. What she does not expect is an electric romantic spark with a Nantucket local, Cal, whose kind heart and charisma have her absolutely smitten. With plenty of her signature Nantucket magic, Nancy Thayer brings both Eleanor and Ari on a summer beyond their wildest imaginations, filled with exciting connections, old and new"--